Factors of Development of Creative Ability of Higher Education Students (Texas Journal of Engineering and Technology, 2022)
In the article, the essence of developing creative ability of students, many social and personal factors, including psychological characteristics, character, will, ingenuity, and passion, in the process of higher education is highlighted.